The Early Assurance Program Model for Physical Therapy Education. Issue 3 (2017) - Chevan, Julia; Reinking, Mark; Iversen, Maura Daly
Abstract : Background and Purpose. : Early assurance programs for entry‐level education of physical therapists (PTs) have existed since academic programs of study were initiated in physical therapy at the college and university level. These programs provide a unique approach to student education that incorporates a bachelor's and a doctoral degree into a single seamless educational experience. This article describes the early assurance model in physical therapy education and aims to demonstrate the advantages of this model using Astin's Inputs‐Environment‐Outputs (I‐E‐O) framework. Position and Rationale. : Early assurance programs provide students who demonstrate academic acumen in high school with a mechanism of entry that guarantees a seat in a PT educational program as long as students meet progression standards. We describe the programs using the I‐E‐O framework. The inputs are the admissions characteristics of students who are entering these programs directly from high school. The environment characteristics include the types of institutions that house these programs and the timing and coursework included in the programs. The outputs or outcomes of early assurance programs, including graduation rates, employment rates, and NPTE pass rates, are comparable to programs that offer traditional graduate admission. The physical therapy education community, secondary education institutions, and current and prospective students all benefit from having this educational option available. Discussion and Conclusion. : Students in early assurance programs are confident in their career paths, have ample opportunity for interprofessional interactions, engage with physical therapy faculty early in their academic career, and develop professional behaviors as they mature and enter the profession.